Colour Reaction of p-Acetylchlorophosphonazo with Strontium(II) and Analytical Application - Zhai, Qing-Zhou (Asian Journal of Chemistry, 2012)
A simple and sensitive spectrophotometric method for the determination of strontium has been developed using p-acetylchlorophosphonazo (CPApA) as chromogenic agent and optimum reaction conditions along with analytical properties parameters have been established. CPApA with strontium(II) forms a blue complex in CH3COOH-CH3COONa buffer solution at pH = 3.5. At maximum absorption wavelength of the complex of 600 nm, absorbance being determined, a good linear relationship is presented over the range 1-20 μg of strontium(II) in 10 mL with a correlation coefficient of 0.9996. Its regression equation is: A = 0.0499C (C: μg/10 mL) + 0.0211. The apparent molar absorption coefficient of the method is e660 nm = 4.45 × 104 L mol-1 cm-1 and its detection limit is 0.126 μg/mL. The composition of complex is n(CPAPA) : nSr2+ = 2:1 determined respectively by molar ratio method and the equimolar continuous variation method. The method has been successfully applied to the determination of strontium content in KCl and Na2SO4 chemical reagents. The results were compared favourably with those obtained by atomic absorption spectrometric method.